2017
DOI: 10.1002/oby.21895
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Consuming Foods Predicts Changes in Cravings for Those Foods During Weight Loss: The POUNDS Lost Study

Abstract: Objective-Food cravings are thought to be the result of conditioning or pairing hunger with consumption of certain foods.Methods-In a two-year weight loss trial, subjects were randomized to one of four diets that varied in macronutrient content. The Food Craving Inventory (FCI) was used to measure cravings at baseline, 6, and 24 months. Also, food intake was measured at those time points. To measure free-living consumption of food items measured in the FCI, items on the FCI were matched to the foods consumed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
(60 reference statements)
2
12
0
Order By: Relevance
“…As it relates to food cravings and dietary quality or obesity, most published studies are behavioral interventions that evaluate cravings as a potential intermediary for brain processes related to dietary quality and/or reducing energy intake among adults [17] or specifically adults with obesity [18]. There is limited evidence of specific healthy or unhealthy cravings being directly linked to dietary quality in any age group.…”
Section: Introductionmentioning
confidence: 99%
“…As it relates to food cravings and dietary quality or obesity, most published studies are behavioral interventions that evaluate cravings as a potential intermediary for brain processes related to dietary quality and/or reducing energy intake among adults [17] or specifically adults with obesity [18]. There is limited evidence of specific healthy or unhealthy cravings being directly linked to dietary quality in any age group.…”
Section: Introductionmentioning
confidence: 99%
“…Although a few WL studies suggest cravings may not change [4] or even increase [5,6], a large number of clinical trials, most from 12 weeks to 2 years in duration, have demonstrated that cravings are reduced during energy restriction [5,[7][8][9][10][11][12][13][14][15][16][17][18]. Some authors have reported that greater WL is associated with greater reductions in food cravings [11][12][13], while others have found no relationships [5,19]. With regard to dietary macronutrient content, of the three studies investigating low-CHO diet effects on food cravings, two reported reduced cravings [11,15], while one [5] reported increased cravings.…”
Section: Introductionmentioning
confidence: 99%
“…Reducing number of HED foods consumed reduces dietary variety of these foods, which reduces food cravings, and increases habituation to these foods. 21 Moreover, this strategy helps consumers develop food environments that align with healthier decisions, requiring them to exert less willpower to reduce dietary ED. 30 Thus, these goals, increasing number of LED and decreasing number of HED foods consumed, may assist with satiation, while reducing problematic factors (food cravings, environmental cues) for dietary adherence.…”
Section: Discussionmentioning
confidence: 99%
“…20 Having goals for the number of different LED and HED foods to consume may be easier to implement than shifting the proportions of LED and HED foods used in recipes to reduce the ED of a meal. 21 In addition, reducing dietary ED by reducing the number of HED foods consumed may reduce the HED variety and reduce the frequency of exposure to HED foods, potentially limiting food cravings. 8,21 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation